Does a Highly Leveraged Capital Structure of a Firm Influence Its Performance? – A Comparative Study of High and Low Leveraged FMCG Companies in India - Peswani, Shilpa (Indian Journal of Finance, 2011)
The research paper is based on research conducted of 2 best companies in the FMCG sector to analyze whether capital leveraging influences the profitability of the companies. As observed through the analysis that though Marico Industries Limited is a high leveraged firm than Britannia Industries Limited, their CAGR has been approximately the same. Definitely, a high leverage firm is able to provide better Return on Equity to its shareholders but the profitability of both the companies is similar. So basically, it is the capabilities of the management to employed the capital optimally that influences profitability of the company rather than the source of capital that is required to be invested in the business strategies of the company.